If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24y + 60 = -5 + -6 Reorder the terms: 60 + 24y = -5 + -6 Combine like terms: -5 + -6 = -11 60 + 24y = -11 Solving 60 + 24y = -11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + 24y = -11 + -60 Combine like terms: 60 + -60 = 0 0 + 24y = -11 + -60 24y = -11 + -60 Combine like terms: -11 + -60 = -71 24y = -71 Divide each side by '24'. y = -2.958333333 Simplifying y = -2.958333333
| 6-6b+b+5=1-3b | | 28000+3000x=7000x+18000 | | 49x-27=2-1.5 | | -(4m-3)=-3(m-2) | | 28000+3000x=6000x+18000 | | 28000+3000x=8000x+18000 | | 28000+3000x=5000x+18000 | | 28000+3000x=1600x+18000 | | 3+6x-2x=35 | | 28000+3000x=1000x+18000 | | 14x+7y=0 | | 28000+3000x=200x+18000 | | 4(2x-1)=68 | | 28000+3000x=3000x+18000 | | 7x+6(x-4)=x | | 28000+3000x=2500x+18000 | | N-4n+2=20 | | 28000+3000x=2000x+18000 | | 28000+3000x=3500x+18000 | | 4.7x+6(x-4)=x | | 8(t-7)-3(t-4)=6(t-7)+8 | | (7P+1)X^2+(5P-1)X+P=1 | | -6(m-6)=-8(m-1) | | 5-3(x-4)=16 | | f(x+1)=2x^2+3x-4 | | 4(2n-3)=20 | | 25.50+6p=45 | | 25x^2-30x-7=-7 | | 5r=53 | | 2x+105+2x+70+x+8+105=360 | | s+s=10 | | 5-2y=0 |